Linear Codes over Finite Rings - de Andrade, A.A.; Palazzo Jr., R. (Trends in Computational and Applied Mathematics, 2005)
In this paper we present a construction technique of cyclic, BCH, alternat, Goppa and Srivastava codes over a local finite commutative rings with identity.